Linguistic awareness in multilinguals : English as a third language - Jessner, Ulrike (Edinburgh University Press, 2006)
This book discusses cognitive and psycholinguistic aspects of third language acquisition and trilingualism, and explores the key role of linguistic awareness in multilingual proficiency and language learning. In view of the widespread acquisition of English by those who are already bilingual or are also acquiring a regional lingua franca this study will contribute to the current discussion of multilingualism with English in Europe and beyond, as well as the understanding of multilingual speech processing. The author supports a dynamic view of multilingualism by stressing the cognitive advantages that the contact with more languages can offer and uses this approach as the basis for future language teaching and learning. Chapters cover topics such as performing in a third language, metalinguistic awareness in multilinguals and in multilingual education, and English as a third language in Europe. Key Features: The first study of the important role metalinguistic awareness plays in multilingual proficiency Includes a unique comparison of both second and third language acquisition Useful for students and scholars of applied linguistics, language education, language planning, psycholinguistics, cognitive linguistics and the study of the English language.